(NoSNOWY NAWIGACII PO GEOFIZI^ESKIM POLQM (B/s - (NbELOGLAZOW(B, (NiNNOKENTIJ nIKOLAEWI^s; (N~IGIN(B, (NgENNADIJ pAWLOWI^s; (NkRASOWSKIJ(B, (Na(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1985)
(NbIBLIOGR(B.: (NS(B. 319-328s
Keywords: (NnAWIGACIONNYE SISTEMY INERCIALXNYEs; (NgEOFIZI^ESKIE ISSLEDOWANIQs